STEM CELLS IN VETERINARY MEDICINE – FROM BIOLOGY TO CLINIC - Majdič, Gregor (Slovenian Veterinary Research, 2018)
Mesenchymal stem cells are adult stem cells found in different adult tissues such as adipose tissue, bone marrow, and also in umbilical blood. Mesenchymal stem cells are capable of differentiation into bone, cartilage and adipose tissue, and several reports also suggest that mesenchymal stem cells might be capable of transdifferentiation into muscle and neural cells. In addition to differentiation potential, mesenchymal stem cells might have other beneficial properties for pathological processes and studies in recent years suggest that mesenchymal stem cells have immunomodulatory, antiinflamatory and trophic actions, contributing to the healing processes in injured/diseased tissues. Osteorthritis is a chronic, progressive disorder with debilitating effects in both animals and humans. It is particularly common in some dog breeds, but also fairly common in humans. Currently, there is no cure for such conditions, but studies in recent years in both human and veterinary medicine suggest that mesenchymal stem cells might have beneficial effect on chronic osteoarthritis. In our laboratory, we have developed a novel method of treating osteoarthritis using autologous adipose tissue derived mesenchymal stem cells in dogs and horses. Stem cells are collected from patients’ adipose tissue, prepared in the laboratory and injected directly into affected joint(s). To prove the efficacy if this method, we have performed blind placebo study in dogs with bilateral osteoarthritis in knees, by treating one knee with stem cells and other knee with placebo (buffer used for cell delivery). Results of clinical examination revealed beneficial effect of stem cell treatment in osteoarthritic knees and x-ray imaging, and although with some limitations, results do suggest that degenerative processes in the knees treated with stem cells were limited or even reversed by the application of stem cells. Stem cells hold a great promise for the future of regenerative medicine, both veterinary and human, however, many questions about their use, potential and efficacy remain open and these will have to be studied and answered in the future years. Key words: dog; horse; stem cells; veterinary medicine